The Integration of Deep Learning into Islamic Education to Strengthen the Religiosity of Muslim Students at Lirung Inpres Public Elementary School within the Framework of Islamic Education - Kasmawati; Sitti Jamilah Amin; St. Aminah; Firman; Fidrayani (International Journal Labs, 2026)
Islamic Religious Education (Pendidikan Agama Islam [PAI]) in Muslim-minority areas requires a pedagogical approach that fosters students’ understanding, internalization, and application of Islamic teachings. This study examined the integration of Deep Learning as a pedagogical approach rather than as computer technology or artificial intelligence, emphasizing mindful, meaningful, and joyful learning. The novelty of the study lies in linking this pedagogical approach to the development of Muslim students’ religiosity in a minority context. Specifically, the study analyzed the implementation of PAI instruction, students’ religiosity, the approach’s impact on each dimension of religiosity and Islamic identity, and the factors supporting and constraining its implementation. This study employed a qualitative approach using an intrinsic case study design. Informants were selected through purposive sampling and included the principal, the PAI teacher, and Muslim students. Data were collected through interviews, observations, and document analysis and were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, conclusion drawing, and verification. The trustworthiness of the data was enhanced through source and method triangulation, member checking, and the use of reference materials. The findings showed that: (1) PAI instruction integrated mindful, meaningful, and joyful learning through reflective questions, connections to students’ lived experiences, stories, videos, quizzes, games, and reflective activities; (2) students’ religiosity was reflected in the dimensions of religious belief, worship practices, religious experience, religious knowledge, and religious behavior; (3) the approach strengthened students’ beliefs, promoted consistent worship practices, fostered positive religious experiences, enhanced religious knowledge, encouraged religious behavior, and reinforced students’ confidence in maintaining their Islamic identity; and (4) implementation was supported by the principal’s leadership, parental support, teacher competence, learning media, worship facilities, a tolerant school environment, and students’ enthusiasm, but was constrained by unreliable electricity, limited internet access, inadequate facilities, variations in students’ religious competence, limited parental guidance at home, and the challenges associated with the Muslim-minority context.